The Development of RME-Worksheets on Multiplication Material for Primary School Students - Desy Puspa Sary; Euis Eti Rohaeti; Nelly Fitriani ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Student Worksheets (LKPD) are teaching materials that help teachers deliver content to students. With LKPD, students find it easier to understand the material and become more motivated in the learning process. However, in practice, teachers are accustomed to using LKPDs purchased from book sales representatives, which often fail to present contextual problems as the starting point of the learning process. This study aims to produce valid teaching materials in the form of LKPD using the Realistic Mathematics Education (RME) approach on multiplication material for elementary school students. The research follows a design research method of the  development studies type. This study was limited to prototype 2, which underwenta formal review by three experts:  two senior teachers as subject matter experts and one lecturer as an education expert. using an expert validation instrument. The data collection technique used was qualitative data obtained from observations and interviews. The results show that the developed LKPD is very valid. It achieved an average validity score of 90%, placing it on the Very valid catagory. these findings contribute to the field of mathematics education by providing a proven, RME-based framework for LKPD design that bridges the gap between abstract multiplication  concepts and real-world application, offering apractical alternative to  commercial worksheets.